Impacts Of Reuses Of Agriculture Drainage Water In Irrigation On Salinity And Sodicity On Alluvial And New Reclaimed Soils In Sharqia Governorate - Mostafa Mahmoud Abobakr Soliman; Mohamed Abdel-Aty Sayed; Ibrahim Mohamed Habib; Nader Noureldeen Mohamed (2024)
The objective of this work is to study the impacts of using agricultural drainage water in irrigation even direct or after blending with fresh water compared with using fresh water on soil salinity and sodicity. This field study takes place for four continuous seasons in old alluvial soil of the Nile Delta and new reclaimed sandy soils. The reuse study has gone under surface flooding irrigation and drip irrigation with five different drains water, in addition to one type of blended water compared with using fresh water. A column experiment was applied to test the field results of calculated traditional leaching fraction and its suggested modifications in leaching the salts that were added by poor quality water. Leaching fraction means adding extra amounts over the regular irrigation water to leach out amounts of salts from soil equal to that added by using poor quality water, could be calculated to keep the soil salinity as it is without increment in case of cultivating salt tolerant crops such as barley and sugar beet. It may also be calculated to decrease the soil salinity to be below the critical salinity level of 4 dS/m to make the soil suitable for cultivating wide numbers of economic field crops in case of high soil salinity.
(3CLQjJ gPg GdOQGSI GdMbdjI dJMOjO JCKjQ GSJNOGe ejGg GdeUGQa GdRQGYjI deOO WhjdI aj GdQj Ydi edhMI hUhOjI GdJQH GdRQGYjI hJMOjO GMJjGLGJ eNUU GdZSjd, dZSjd GdCedGM ef GdJQHI hGdJj JVGa eY gPg GdfhYjI GdabjQI ef ejGg GdQj(B. (3JeJ CjVG OQGSI JCKjQGJ GdQj HGdejGg GdeNdhWI hGdechfI ef ejGg GdeUGQa eY ejGg GdJQY hcPG GdQj HejGg GdJQY abW hJMOjO eNUU GdZSjd dcd fhY ef gPg GdejGg, hPdc defY JQGce hRjGOI edhMI GdJQHI(B. (3CLQjJ GdOQGSI deOI CQHYI ehGSe RQGYjI eJJGHYI GKfJGf aj GdehSe GdTJhj heKdgeG aj GdehSe GdUjaj(B. (3CTGQJ GdfJGFL Edj JRGjO cejI GdCedGM GdeVGaI ddJQHI YfO GSJNOGe ejGg GdeUGQa GdRQGYjI eHGTQI aj GdQj Yf eKjdGJgG YfO GdQj HGdejGg GdeNdhWI hcPdc Yf GSJNOGe GdejGg GdYPHI aj GdQj, hddJCcjO ef bje eNUUGJ GdZSjd GdeMShHI aj GdYed GdMbdj Je ELQGA JLQHI ZSjd eYedjI dCYeOI ef GdJQHI ZjQ GdeSJKGQI GdeCNhPI ef GdMbhd GdSGHbI HfaS JQJjH WHbGJgG hJe JWHjb eYOdGJ GdZSjd GdeMShHI YdjgG ddJCcO ef UMI hJWGHb MSGHGJ eNUUGJ GdZSjd ddhGbY GdMbdj hgh eG CKHJJg GdJLQHI GdeYedjI(B.s
Thesis (M.Sc.) -Cairo University, 2024.
Bibliography: pages 83-93.
Issued also as CD
Text in English and abstract in Arabic & English.
Keywords: Agricultural Sciences; (3GdYdhe GdRQGYjI s; Reuse - drainage water -- blended water -- irrigation efficiency; (3GYGOIs -- (3ejGg GdUQa s -- (3GdejGg GdeNdhWIs